INTERAKSI PELAKU DAUR ULANG SAMPAH MELALUI UJI REGRESI LINEAR DI KELURAHAN PANGGUNG LOR, KUNINGAN DAN BANDAR HARJO KOTA SEMARANG - Maryono, Maryono; Andriyani, Riki (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2010)
Recycling  process  and  activities  are  part  of  the  solid  waste  management.  Informal  Actor  such  as Scavengers,  Small  Middleman  and  Big  Middleman  has  a  unique  networking.  The  interaction  can beclassified  as node, subpoint and centerpoint. They has a relationships which representation of solid waste  transport  among  area  and  region.  Based  on  Sejati  research  (2009),  the  networking  and relationships among the informal actor of Recycling process like can be astimated as a mathematic model. Regrestion analysis was running to test the mathematic model. Panggung Lor, Bandarharjo and  Kuningan,  at  Semarang  was  chosen  as  location  study  because  of  the  characteristic  of  the Recycling activities.